IMPLEMENTASI PROGRAM PENGEMBANGAN PARIWISATA - Arie Gunadi; Zaili Rusli (Jurnal Kebijakan Publik, 2022)
Rokan Hulu Regency which has a very rich natural potential in the aspect of tourism, but this potential is not well managed because many designed programs have not been implemented. This study aims to analyze the implementation of the Rokan Hulu Regency Destination Development program. The method used is a qualitative method where this method refers to research that produces data that cannot be realized in the form of numbers, but in the form of an explanation that describes certain conditions, processes, events. The results showed that the implementation of the tourism development program in Rokan Hulu Regency had not been effective, because the program's objectives could not be achieved, one of which was due to limited budget and human resources in its implementation. The existing road access is not good. The purpose of visitors coming to Hapanasan Hot Springs, there are several objects that can be visited either to enjoy hot springs for therapy and bathing, the beauty of natural forests, tree houses, a small butterfly museum and also local specialties, namely processed kolang-kaling. There are no supporting facilities for lodging and restaurants, only snack stalls.